Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand